جرائم الغش التجاري الواقعة على المستهلك - لوالي, خالد; معاشي, أسماء (Ibn Khaldun University of Tiaret, 2021)
يعتبر الغش التجاري من أبرز الظواهر السلبية وأكثرها انتشارا في المجتمع، ولا يكاد يخلوأي تشريع من تجريم هذه الظاهرة، التي أصابت المستهلك في مأكله ومشربه وملبسه وأغلب متطلبات حياته الضرورية منها والكمالية، ومع تقدم أساليب الإنتاج والتصنيع تطورت أساليب ووسائل الغش والتحايل على المستهلكين من قبل المتدخلين في العملية الاستهلاكية. والمشرع الجزائري على غرار التشريعات المقارنة رصد جملة من القوانين وعلى رأسها قانون العقوبات وقانون حماية المستهلك وقمع الغش لحماية المستهلك حماية موضوعية من خلال تجريمه للخداع والغش و كذا حيازة مواد مغشوشة دون مبرر شرعي، وحماية إجرائية تتمثل في استحداث هيئات رقابية منها ما هي مركزية ومنها ما هي محلية لقمع الغش التجاري، كما خول المشرع الجزائري للقضاء صلاحية متابعة جرائم الغش التجاري وفق إجراءات خاصة بدءا بتحريك الدعوى العمومية مرورا بمحاضر الشرطة القضائية ومحاضر الجهات المكلفة بحماية المستهلك، انتهاء بمرحلتي التحقيق والحكم. Commercial fraud is one of the most important and prevalent negative phenomena in society, and hardly any legislation is exempt from criminalizing this phenomenon, which has plagued consumers in their food, drink, clothing and clothing. most of the necessary and luxury needs of his life. in the process of consumption. The Algerian legislator, like the comparative legislation, controls a certain number of laws, foremost among which the Penal Code, the Law on the protection of the consumer, and the repression of the fraud to protect the consumer objectively by criminalizing the deception and fraud, as well as possession of fraudulent products. materials without legal justification, and procedural protection represented in the creation of control bodies, some of which are central and others It is local to suppress commercial fraud The Algerian legislator has also empowered the judiciary to prosecute fraud offenses commercial according to special procedures, starting with the opening of the public case, passing through the records of the judicial police and the archives of the bodies responsible for consumer protection, ending with the phases of investigation and judgment
Keywords: Droit de la consommation